The chemistry and bioactive properties behind microalgae-enriched gluten-free breads - Freitas, Marco A. (2023)
This work aims to: (i) assess volatiles composition of microalgae-enriched gluten-free breads (prepared with Tetraselmis chuii, Chlorella vulgaris and Microchloropsis gaditana); (ii) report the bioaccessibility of protein and minerals after a static in vitro digestion model; (iii) understand how it affects the bioactive properties of gluten-free breads in regard to antioxidant capacity and the α-amylase inhibitory potential. Therefore, nutritional composition and bioactive properties of gluten-free breads before and after in vitro digestion model were examined. Identification of compounds responsible for the overall aroma of microalgae using GC–MS was done. There was a considerable decrease in protein and minerals available after in vitro digestion, as well as in the antioxidant potential. The overall aroma of microalgae-enriched breads was mainly due to the presence of alcohols, representing the major class of volatiles present in breads (3% to 59%), being lower for T. chuii-enriched bread. Terpenes also existed in considerable amounts especially in M. gaditana (24%) where γ-terpinene was the most abundant. Alkanoic acids were the most abundant lipophilic bioactive compounds (25%–68%), and 9,12-octadecadienoic acid was the major identified compound (13%–51%). Phytic acid is also present in all microalgae-enriched breads and may contribute to the decrease in the bioaccessibility of nutrients.